Perancangan Sistem Informasi E-Arsip Dokumen Berbasis Codeigneter Pada Divisi Pertanahan Di PT. Deltacendana Citapersada - Puput Julyanti; Sigit Auliana; Basuki Rakhim Setya Permana (PPPM Institut Teknologi Pagar Alam, 2025)
The development of information technology has encouraged organizations to shift from conventional archive management systems to more efficient and integrated digital systems. PT. Deltacendana Citapersada, particularly in the Land Division, still faces obstacles in manually managing important document archives, such as the risk of data loss, slow searches, and lack of access control. This study aims to design and develop a web-based document e-archive information system using the CodeIgniter framework to improve the effectiveness and efficiency of the archiving process. This study uses a descriptive method with a field study approach through observation and interviews. System development is carried out using the Waterfall model, through the stages of needs analysis, system design, interface implementation, and testing. The system built includes role-based login features, category management, multi-format document uploads, archive searches, and user management. Testing results using the black box method show that all system functions run according to specifications, and User Acceptance Testing (UAT) testing shows a user satisfaction level of 89.47%, which indicates the system is well received. This study concludes that the designed e-archive system has successfully replaced conventional archiving methods with a more efficient and structured e-archive system. This transition overcomes various problems in manual archiving, such as the difficulty of searching for documents, the risk of archive loss, and the potential for document damage due to human error or environmental factors. Therefore, the developed digital system is deemed feasible for implementation as a modern and reliable archive management solution. For further development, it is recommended to add notification features, integrate with cloud storage services, and provide user training to maximize system utilization.